Dealer-based brand equity: The role of market orientation and relationship marketing on brand equity - Abd Ghani, Noor Hasmini; Mohamad, Osman (INSInet Publications, 2014)
This study is to investigate the role of relationship marketing and market orientation strategy in developing brand equity from the dealer’s viewpoint, focused on automobile authorized independent sales dealers in Malaysia.Interestingly, the finding showed market orientation influenced the brand equity.But, the brand equity formation is by a function of relationship marketing and not restricted to the direct role of market orientation.Hence, to support the growth of both dealers and their firm’s future success, the study highlighted that relationship marketing activities is needed in any company’s strategy including in training activities as well as marketing events.